OpaR Controls the Metabolism of c-di-GMP in Vibrio parahaemolyticus - Zhang, Yiquan; Qiu, Yue; Gao, He; Sun, Junfang; Li, Xue; Zhang, Miaomiao; Xue, Xingfan; Yang, Wenhui; Ni, Bin; Hu, Lingfei; Yin, Zhe; Lu, Renfei; et al. (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus, the leading cause of seafood-associated gastroenteritis worldwide, has a strong ability to form biofilms on surfaces. Quorum sensing (QS) is a process widely used by bacteria to communicate with each other and control gene expression via the secretion and detection of autoinducers. OpaR is the master QS regulator of V. parahaemolyticus operating under high cell density (HCD). OpaR regulation of V. parahaemolyticus biofilm formation has been reported, but the regulatory mechanisms are still not full understood. Bis-(3'-5')-cyclic di-GMP (c-di-GMP) is an omnipresent intracellular second messenger that regulates diverse behaviors of bacteria including activation of biofilm formation. In this work, we showed that OpaR repressed biofilm formation and decreased the intracellular concentration of c-di-GMP in V. parahaemolyticus RIMD2210633. The OpaR box-like sequences were detected within the regulatory DNA regions of scrA, scrG, VP0117, VPA0198, VPA1176, VP0699 and VP2979, encoding a group of GGDEF and/or EAL type proteins. The results of qPCR, LacZ fusion, EMSA and DNase I footprinting assays demonstrated that OpaR bound to the upstream DNA regions of scrA, VP0117, VPA0198, VPA1176 and VP0699 to repress their transcription, whereas it positively and directly regulated the transcription of scrG and VP2979. Thus, transcriptional regulation of these genes by OpaR led to directly to changes in the intracellular concentration of c-di-GMP. The direct association between QS and c-di-GMP metabolism in V. parahaemolyticus RIMD2210633 would be conducive to precise control of gene transcription and bacterial behaviors such as biofilm formation.